Implementation of Web-Based Furniture Store Management Information System - Dwimaelani, Riska; Riadi, Aditya Akbar; Susanto, Arief (Newinera Publisher, 2025)
In the era of increasingly rapid digitalization, the need for efficient and integrated business management is becoming increasingly important. Companies that are able to manage data systematically and in real-time have a competitive advantage in facing market competition. Alma Jati Mebel Pati, as a business actor in the furniture industry sector, faces challenges in the operational management process, such as manual transaction recording, non-centralized stock management, and difficulties in making fast and accurate sales reports. This study aims to develop and implement a web-based furniture store management information system to improve the efficiency and effectiveness of the company's operations. This system is built using the Waterfall method which consists of several stages, namely needs analysis, system design, implementation, and testing. The technologies used include PHP as a programming language, MySQL as a database management system, Laravel as a backend development framework, and Bootstrap for a responsive and user-friendly interface. This system is equipped with main features such as recording sales and purchase transactions, product stock management, and financial report generation. Testing was carried out using the Black Box Testing method to ensure that the system's functionality runs according to user needs. The test results show that all features function properly without significant errors. In addition, the usability test conducted on users resulted in a satisfaction rate of 85%, indicating that the system is easy to use and helpful in daily work processes. With this system, Alma Jati Mebel is expected to optimize business management more effectively, efficiently, and integrated.